Impact of neoadjuvant systemic therapy on surgical and radiotherapy outcomes in patients with early-stage breast cancer: a cross-sectional retrospective single-center study - Yasmin A. Civil; Katya M. Duvivier; Sanne A. L. Bartels; Susanne van der Velde; C. Willemien Menke-van der Houven van Oordt; Ellis Barbé; Suzan van der Meij; Berend J. Slotman; Desirée van den Bongard (BMC Cancer)
Abstract Introduction Neoadjuvant systemic therapy (NST) may cause non-concentric tumor shrinkage, complicating excision volume definition and potentially increasing radiotherapy boost volumes, affecting cosmetic outcomes. This study aims to compare excision and boost volumes in patients undergoing breast-conserving surgery (BCS) after NST versus no-NST, and assesses associations with quality of life (QoL) and cosmetic outcomes. Methods Women who underwent BCS for invasive breast cancer at Amsterdam UMC (January 2016-March 2023) were included. Data were retrieved from records, and cross-sectional QoL and cosmetic outcomes were assessed using EORTC-QLQ-C30, -BR23, HADS and BREAST-Q questionnaires. Descriptive statistics were stratified by NST use, with sensitivity analyses for robustness. Excess healthy tissue removal was defined by the calculated resection ratio (CRR) (derived from excision volume and tumor diameter). Results Among 403 patients, 136 (33.7%) received NST. Median pathological (postoperative) tumor size was smaller in the NST group (7 mm vs. 14 mm, p < 0.001). NST was associated with smaller total resection volumes (TRVs) in patients with cT2 (35 cm3 vs. 53 cm3, p = 0.005), and HER2-positive tumors (20 cm3 vs. 79 cm3, p = 0.048). CCRs were higher (2.2 vs. 1.6, p < 0.002), and radiotherapy boost volume were lower (55 cm3 vs. 91 cm3, p = 0.009) following NST. Additionally, fewer patients in the NST group reported acute breast pain (16% vs. 20%, p = 0.029). Breast satisfaction scores according to the Breast-Q were 9 points higher in the NST group, although not statistically significant (p = 0.157). Conclusion NST reduced TRVs in cT2 and HER2-positive tumors, and decreased radiotherapy boost volumes in all patients. However, it was also associated with increased removal of healthy breast tissue. Despite this, NST as associated with less acute breast pain and clinically meaningful improvements in breast satisfaction. Clinical trial number Not applicable.